Konstruksi Hukum Adat Pernikahan Masyarakat Melayu Palembang Berdasarkan Syar’iat Islam - Ahmad Fahmi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2019)
Marriage is one of the tiers in the life of the society which called “stage a long the life cycle”. The purpose of this research is to obtain the informationa about: First, The Customs Procedures of Marriage for Melayu Palembang People; Second, Islamic Law in Marriage Customs for Melayu Palembang People; Third, The Customs Culture of Marriage for Melayu Palembang People; and Fourth, The Islamic Construction of Marriage Customs for Melayu Palembang People. This Research is using Qualitative Research Methods with Law Sociologist approachment and Islamic Idea, which is focused to the implementation process of marriage based on Islamic and Culture law with performance goals that have been set. The Research several Data was obtained by using interview method which was done to the object of respondent. The results of this research show : First, The customs procedures of marriage for Melayu Palembang people, in the implementation, are use Islamic law however there are some choreography by itself such as pre-marriage and after marriage. The culture of marriage for Melayu Palembang people, is divided into four phases: Cultural phase pre-marriage, Cultural phase implementation of marriage, Cultural phase after marriage and pattern of settling after marriage. Second, Marriage Law in Islamic religious teachings with Matrial Law in the state law, in marriage ordinances of Melayu Palembang people in general can be said to have been aligned, in its implementation also in accordance with the rules and referral. Where as the references in the state law on marriage are Al Quran, Al Sunnah and Qaidah Fighiyah and Consesus of Muslims in Indonesia. Third, Contribution of customary law appears on before and after marriage where there are certain or dinances and there are certain ways to hold the marriage. The customary law of our country is the laws that suit the development of Islamic Society in Indonesia, customary marriage for Melayu Palembang people on its implementation is the application of Islamic Law Theory. Fourth, Construction of Islam in marriage maintained, that marriage has values that are preserved by Melayu Palembang people continuously. The value of faith in Islamic Marriage is a good act and behavior and can lead toward the marriage in the religion of Islam, namely to evoke marriage that enriches sakina, mawada, warahmah and barokah. The points contained in the religion of Islam contains the meaning and the bonding element that have a profund influence on customary marriage of Melayu Palembang people, because this bonds came from the power that comes from the Creator.